Point-of-Care Ultrasound to Assess Gastric Content in Pediatric Emergency Department Procedural Sedation Patients. Issue 1 (January 2022) - Moake, Matthew M.; Presley, Bradley C.; Hill, Jeanne G.; Wolf, Bethany J.; Kane, Ian D.; Busch, Carrie E.; Jackson, Benjamin F.
Abstract : Objectives: There is debate regarding the timing of procedural sedation and analgesia (PSA) in relation to fasting status. Point-of-care ultrasound (POCUS) provides the ability to measure gastric content and is being used as a surrogate for aspiration risk in anesthesia. We sought to evaluate the gastric content of pediatric emergency department (PED) patients undergoing PSA using POCUS. Methods: We performed a prospective observational study using a convenience sample of pediatric patients undergoing PSA between July 1, 2018, and June 30, 2019. Following a brief history, gastric content was measured using POCUS in both supine and right lateral decubitus positions at 2-hour intervals until the time of PSA. Qualitative content and calculated volume were classified based on the Perlas Model of anesthesia "Risk" assessment. Results: Ninety-three patients were enrolled with 61.3% male and mean age of 6.5 years. Gastric content was determined in 92 patients. There were 79.3% that had "high risk" content at the time of PSA, with a median fasting time of 6.25 hours and no serious adverse events. Fasting duration had a weak to moderate ability to predict "risk" category (area under the curve = 0.73), with no patient (n = 17) who underwent multiple evaluations awaiting PSA progressing from "high" to "low risk." Conclusions: The majority of PED patients undergoing PSA at our institution had "high risk" gastric content with no clinically significant change occurring during serial evaluations. This calls into question the utility of delaying PSA based upon fasting status and lends support to a more comprehensive risk-benefit approach when planning pediatric PSA. Abstract : Supplemental digital content is available in the text.